Respuesta :
Answer:
[tex](q^2-r^2s)(q^4+q^2r^2s+r^4s^2)=q^6-r^6s^3[/tex]
Step-by-step explanation:
Given : Expression [tex](q^2-r^2s)(q^4+q^2r^2s+r^4s^2)[/tex]
To find : Factor the expression?
Solution :
The given expression [tex](q^2-r^2s)(q^4+q^2r^2s+r^4s^2)[/tex] is the factored form of [tex]q^6-r^6s^3[/tex]
Now, We solve to get the form
[tex]a^3-b^3=(a-b)(a^2+ab+b^2)[/tex]
Taking RHS and compare with the given expression
[tex](q^2-r^2s)(q^4+q^2r^2s+r^4s^2)[/tex]
Where, [tex]a=q^2,b=r^2s[/tex]
[tex]=(q^2)^3-(r^2s)^3[/tex]
[tex]=q^6-r^6s^3[/tex]
Therefore, [tex](q^2-r^2s)(q^4+q^2r^2s+r^4s^2)=q^6-r^6s^3[/tex]